Are Immigrant and Minority Homeownership Rates Gaining Ground in the US? - Durba Chakrabarty; Michael J. Osei; John V. Winters; Danyang Zhao (Institute of Labor Economics (IZA), 2017)
This paper investigates post-2000 trends in homeownership rates in the US by immigrant status, race, and ethnicity. Homeownership rates for most groups examined rose during the housing boom of the early and mid-2000s but fell during and after the housing bust. By 2015 homeownership rates had fallen below year 2000 levels for most groups but not all. In particular, some Asian immigrant groups experienced sizable gains in overall homeownership rates and in regression-adjusted differences relative to white non-Hispanic natives. Some other immigrant and minority groups also made gains relative to white non- Hispanic natives. We document and discuss these trends.
Keywords: R21; J15; 330; housing; homeownership; immigrants; minorities